Influenza Virus Detection Following Administration of Live-Attenuated Intranasal Influenza Vaccine in Children With Cystic Fibrosis and Their Healthy Siblings. (30th August 2016) - Boikos, Constantina; Joseph, Lawrence; Martineau, Christine; Papenburg, Jesse; Scheifele, David; Lands, Larry C.; De Serres, Gaston; Chilvers, Mark; Quach, Caroline
Abstract: Background. We aimed to explore the detection profile of influenza viruses following live-attenuated intranasal influenza vaccination (LAIV) in children aged 2–19 years with and without cystic fibrosis (CF). Methods. Before the 2013–2014 influenza season, flocked nasal swabs were obtained before vaccination and 4 times in the week of follow-up from 76 participants (nCF : 57; nhealthy : 19). Influenza was detected by reverse transcription polymerase chain reaction (RT-PCR) assays. A Bayesian hierarchical logistic regression model was used to estimate the effect of CF status and age on influenza detection. Results. Overall, 69% of the study cohort shed influenza RNA during follow-up. The mean duration of RT-PCR detection was 2.09 days (95% credible interval [CrI]: 1.73–2.48). The odds of influenza RNA detection on day 1 following vaccination decreased with age in years (odds ratio [OR]: 0.82 per year; 95% CrI: 0.70–0.95), and subjects with CF had higher odds of influenza RNA detection on day 1 of follow-up (OR: 5.09; 95% CrI: 1.02–29.9). Conclusion. Despite the small sample size, our results indicate that LAIV vaccine strains are detectable during the week after LAIV, mainly in younger individuals and vaccinees with CF. It remains unclear whether recommendations for avoiding contact with severely immunocompromised patients should differ for these groups.